2006
DOI: 10.1111/j.1553-2712.2006.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital versus Local Anesthesia for Finger Lacerations: A Randomized Controlled Trial

Abstract: Digital and local anesthesia of finger lacerations with prior application of LET to all wounds results in similar pain of needle insertion, anesthetic infiltration, and pain of suturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…They are preferable to local injections because they require reduced doses of agent and do not involve physical alteration of the tissue in question. 43…”
Section: Common Regional Anesthetic Techniquesmentioning
confidence: 99%
“…They are preferable to local injections because they require reduced doses of agent and do not involve physical alteration of the tissue in question. 43…”
Section: Common Regional Anesthetic Techniquesmentioning
confidence: 99%
“…Regarding the exposure or administration times, although Patterson, in 1998 [ 33 ], reported that the exposure time for topical anesthetics should be 20–30 min for LAT and between 30 min and 2 h for EMLA ® cream, recent studies have suggested the need for a shorter exposure time to achieve anesthesia, with exposure times ranging from 5 or 15 min [ 34 ] to 20 min [ 35 ] for the gel LAT, and 45 min, 60 min [ 17 ], or up to 2 h [ 36 ] for EMLA ® cream.…”
Section: Discussionmentioning
confidence: 99%
“…In another similar study, which mentioned topical anesthesia prior to the actual anesthesia, no differences were observed between digital block and infiltration anesthesia in terms of needle entry, infiltration of medication, or suture pain. In one patient extra anesthesia was required (8).…”
Section: Discussionmentioning
confidence: 99%